ANDROID-BASED SCRAP METAL COLLECTION SYSTEM WITH LIVE-LOCATION TRACKING: A PROTOTYPE APPROACH IN MANADO CITY - Massie Hihola, Maharani Margareth; Pinontoan, Benny; Alfonsius, Eric (IJIS - Indonesian Journal On Information System, 2026)
This research aims to design and develop an Android-based application integrated with real-time location tracking to support scrap metal pickup services. The system was developed using the Prototype method. The application was built with Flutter and Dart, using Firebase as the backend and the Google Maps API for GPS-based real-time location tracking and map visualization. The system offers features for both customers and collectors. Customers can request pickup services, enter information about the scrap they have, choose a collector, and track the collector's location. Collectors get the request, check the service details, and go to the customer's location. These features enable users to communicate and work together on a single digital platform. System testing was conducted using Black-Box Testing with the Equivalence Partitioning technique, with alpha testing involving 6 participants. From 126 test cases, 124 were successful, resulting in a Task Success Rate (TSR) of 98%. These results indicate that the system is functionally reliable in supporting the main processes of scrap metal pickup services. Furthermore, the developed application is expected to facilitate interaction between customers and collectors, provide visibility of collector locations through real-time tracking, and support the implementation of a digital-based scrap metal pickup service.Keywords: Android Application, Live Location Tracking, Scrap Metal Pickup, Prototype Method, Google Maps